A Study of the Nutritional Behavior of Basketball Players in Different Playing Centers of the Western Region Clubs in KSA - El-Saleh, Dr. Majed Saleem; Alabidi , Dr. Suzan; Alqawasmi, Dr. Abdellateef; Alzughailat, Dr. Mohannad (International Journal of Membrane Science and Technology, 2023)
Background /objective: Experts in sports nutrition know that diet significantly influences athletic performance and that all basketball players should adapt specific nutritional strategies before, during and after training and competition to maximize their mental and physical performance. Therefore, this study aimed to identify the nutritional behavior of basketball players in the western region clubs in the Kingdom of Saudi Arabia (KSA) in the premier league according to the different playing centers of the players. Methods: The researcher used the descriptive approach for its suitability to the nature of this study, where a random sample of (48) players was selected from clubs in the western region (Madina / Jeddah), and the study tool consisting of five axes was applied to the sample members during the 2020/2021 sports season.Results: there is a discrepancy in the nutritional behavior of basketball players in the western region, as well as the existence of a correlation between the playing centers and some food behavior axes. Conclusion: There is an existence of a correlation relationship in some aspects of nutritional behavior and playing centers for basketball players in the western region of the KSA.